ANALISIS FAKTOR - FAKTOR PENYEBAB KETERLAMBATAN PELAKSANAAN PEMBANGUNAN PROYEK PONDOK PESANTREN NURUL ILMI KAB. BANYUASIN - Ardiyanti, Murni; Firdaus, Firdaus (Ensiklopedia of Journal, 2023)
In the construction of a building, there are many factors that must be taken into account, one of which is the delay factor in a project, because in the implementation of construction projects things often happen that do not go according to plan, such as delays in completion time. This can result in losses, special attention needs to be paid to delays, so that this can be minimized. This research uses a quantitative descriptive method by conducting interviews and distributing questionnaires to find the factors that most influence the causes of time delays. The data obtained is processed using statistical analysis using SPSS software. From the results of the analysis tests it is found that the variables that are the most influential factors are Design changes made by the owner are delays, lack of labor causes low work results, and cost overruns are the most influential factors. Based on these factors, control efforts are formulated that can minimize this in the form of preventive and corrective actions.